Factores socioculturales y nivel de conocimiento sobre litiasis vesicular en pacientes de cirugía, Hospital III Iquitos EsSalud Punchana 2021 - Aspajo Chávez, Liliana Isabel (2022)
The objective was to determine the relationship between sociocultural factors (age, sex, origin, body mass index) and level of knowledge about gallstones in surgery patients, Hospital III Iquitos Essalud Punchana 2021. The method used was quantitative, non-experimental design, whose sample was 132 surgically intervened patients. The techniques used were the interview, the documentary analysis for the review of the clinical history and the application of the instrument on sociocultural factors and level of knowledge about gallstones with a validity of (86.52%). and a reliability of (89.6%). The results obtained are: 63,6% (84) had a low level of knowledge, 28.1% (37) presented medium level of knowledge and only 8.3% (11) high level of knowledge about gallstones. 59.1% (78) left middle-aged adults, 72.7% (96) were female, 92.4% (122) came from urban, 50% (66) were overweight and 27.3% (36) were obese. It is concluded that there is a statistically significant relationship between age (p = 0.000), sex (p=0.016), origin (p = 0. 000) and Body Mass Index (p = 0.000) with the level of knowledge about gallstones in surgery patients, Hospital III Iquitos Essalud Punchana 2021.